Strategic approaches to halal lipid authentication using instrumental, chemometric, and traceability techniques - Abdullah Sani, Muhamad Shirwan; Mohd Ismail, Azilawati; Azid, Azman; Samsudin, Mohd Saiful; Yuswan, Mohd Hafis; Othman, Muhammad Bisyrul Hafi (AIJR Publisher, 2025)
This book explores the complex field of halal lipids, combining contemporary scientific discoveries with traditional Islamic beliefs. This thorough handbook, which covers everything from lipid extraction and microbial lipid applications to cutting-edge applications in cosmetics and active packaging, is intended for researchers, business executives, legislators, and students. With an emphasis on sustainability and traceability, the chapters examine the scientific, technological, and economic facets of halal lipids. This book offers insights into how science, innovation, and Islamic values may come together to promote growth and consumer trust as the halal business adapts to meet demands from throughout the world.